Human Assistance Mechanism Using Real World Embedded Systems (International Journal of Innovative Research in Computer Science & Technology, 2017)
Home automation suffers from platform  fragmentation and lack of technical standards a situation  where the variety of home automation devices, in terms of both  hardware variations and differences in the software running  on them, makes the task of developing applications that work  consistently between different inconsistent technology  ecosystems hard. Customers may be hesitant to bet their IoT  future on proprietary software or hardware devices that use  proprietary protocols that may fade or become difficult to  customize and interconnect. Home automation or smart home  (also known as domotics or domotica) is the residential  extension of building automation and involves the control and  automation of lighting, heating (such as smart thermostats),  ventilation, air conditioning (HVAC), and security, as well as  home appliances such as washer/dryers, ovens or  refrigerators/freezers that use Wi-Fi for remote monitoring.  Modern systems generally consist of switches and sensors  connected to a central hub sometimes called a "gateway" from  which the system is controlled with a user interface that is  interacted either with a wall-mounted terminal, mobile phone  software, tablet computer or a web interface, often but not  always via internet cloud services. Zigbee has a defined rate of  250 kbits/s, best suited for periodic or intermittent data or a  single signal transmission from a sensor or input device. The  wireless home Automation systems is supposed to be  implemented in existing home environments, without any  changes in the infrastructure. This system is most suitable for  the elderly and the disabled persons especially those who live  alone and since recognize voice so it is secure.
Keywords: Home automation; Microcontroller; Voice Recognition; ZigBee; Power SupplY